Standar Keshahihan Hadis Menurut Syuhudi Ismail - Irham Habib (El-Sunan: Journal of Hadith and Religious Studies, 2023)
This Article aims to discuss Syuhudi Ismail’s view of the standard of authentic hadith. The author uses the library research method. This method uses data collection with the technique of documenting books that discuss Syuhudi Ismail and his method of studying hadith. Furthermore, the results of the study are: Syuhudi Ismail presents two principles in criticizing the authenticity of hadith, namely the major rule and the minor rule. The major rules are the varios conditions of criteria for the validity of a hadith that are general in nature, while the minor rules are the elements of the rules which are derivatives and detailed explanations of the rules major. ABSTRAK Artikel ini bertujuan untuk membahas pandangan Syuhudi Ismail terhadap standar keshahihan hadis. Penulis menggunakan metode kajian pustaka (library research). Metode ini menggunakan pengumpulan data dengan teknik mendokumentasikan buku-buku yang membahas tentang Syuhudi Ismail dan metodenya dalam menelaah hadis. Selanjutnya hasil dari kajian tersebut adalah: Syuhudi Ismail menyajikan dua kaidah dalam mengkiritik keshahihan hadis yaitu kaedah mayor dan kaedah minor. Kaedah mayor adalah berbagai syarat atau kreteria kesahihan suatu hadis yang bersifat umum, sedangkan kaedah minor yaitu unsur-unsur kaedah yang merupakan turunan dan penjelasan terperinci dari kaidah mayor.